High-dose thiamine supplementation ameliorates obesity induced by a high-fat and high-fructose diet in mice by reshaping gut microbiota - Xia, Yu; Wang, Lulu; Qiu, Yanyan; Ge, Weihong (Frontiers in Nutrition, 2025)
IntroductionThiamine (vitamin B1) in the gut is crucial for maintaining intestinal homeostasis and host health. Our previous study identified significantly lower levels of fecal thiamine in individuals with obesity; however, its potential and mechanisms for alleviating obesity induced by a high-fat and high-fructose diet (HFFD) remain unclear. Therefore, in the present study, the effects of high-dose thiamine supplementation on HFFD-induced obesity and gut microbiota dysbiosis were investigated.MethodsHFFD-fed mice were supplemented with high-dose thiamine for eight weeks. Biochemical analysis and histological analysis were conducted to assess phenotypic changes. Fecal 16S rRNA gene sequencing was performed to analyze alterations in the gut microbiota.ResultsThe results showed that high-dose thiamine supplementation for eight weeks could significantly alleviate symptoms of HFFD-induced obesity and improve HFFD-induced intestinal epithelial barrier dysfunction by enhancing the tight junction function. Furthermore, oral administration of high-dose thiamine also regulated HFFD-induced gut microbiota dysbiosis by reshaping its structure and composition of gut microbiota, such as increasing the relative abundance of Actinobacteria and Bifidobacterium pseudolongum, and reducing the relative abundance of Proteobacteria and Ruminococcus gnavus, accompanied by decreased level of gut-derived endotoxin. Finally, significant correlations were found between obesity-related phenotypes and gut microbiota through correlation analysis.ConclusionOur findings suggest that the potential mechanism by which high-dose thiamine supplementation alleviated HFFD-induced obesity might involve reshaping gut microbiota and restoring the intestinal barrier, thereby ameliorating gut microbiota-related endotoxemia.